Removal of naphthenic acids using activated charcoal: Kinetic and equilibrium studies - Natália F Campos; Celmy MBM Barbosa; Joan M Rodríguez-Díaz; Marta MMB Duarte (Adsorption Science & Technology)
This study proposes the use of activated charcoal made from Umbaúba wood as an adsorbent for the removal of naphthenic acid in an aviation kerosene model mixture. The activated charcoal was characterised as mesoporous with a carbon graphite profile and presented pH pzc equal to 10.5. The best working conditions were obtained for activated charcoal levels of <0.09 mm and 300 r min −1 . The system reached the equilibrium after 360 min, without significant statistical difference for the pseudo-first- and pseudo-second-order kinetic models. The Weber–Morris and Boyd models corroborated the conclusion that adsorption is not controlled only by the intraparticle diffusion step. For the equilibrium study, the adsorptive capacity obtained was of 1.1 g g −1 , with the Brunauer–Emmett–Teller model better correlating with the experimental data. Given the results obtained, the activated charcoal demonstrated to have a remarkable potential for removing naphthenic acid in an aviation kerosene model mixture.